Legal Reconstruction of Voter Abstention in Indonesia: Comparative Insights from MUI Fatwa and Electoral Law - Sistyawan, Dwanda Julisa; Safriani, Laela; Judijanto, Loso; Saputra, Edy; Ridwan, Mohammad; Pakarti, Muhammad Husni Abdulah (UNISSULA, 2024)
This study aims to examine the phenomenon of voter abstention, known as voter abstention (Golongan Putih or Golput), from the perspectives of Islamic law and Indonesian electoral legislation. The research utilizes a qualitative approach, relying on literature reviews and primary governmental documents to analyze how these two legal frameworks address and regulate voter abstention. The study explores the intersection of Islamic jurisprudence, particularly the 2009 fatwa by the Indonesian Ulama Council (Majelis Ulama Indonesia or MUI) that declared Golput haram (forbidden), and Indonesia’s electoral law, specifically Law No. 7 of 2017, which encourages voter participation without penalizing abstention. The findings reveal that while Golput is not prohibited by electoral law, it is framed as a violation of religious duty within Islamic legal thought. Additionally, the study highlights Golput as a form of civil resistance and political expression in Indonesia's democratic system. The analysis of these dual legal systems provides insights into the complexities of voter behavior and presents recommendations for strengthening democratic engagement. The implications of this research suggest that integrating religious principles with legal norms could enhance voter turnout and foster more inclusive electoral participation in Indonesia.